pengaruh discovery learning terhadap hasil belajar siswa pada materi tekanan dengan bantuan media phet interactive simulation - Sinaga, Golberd Harmuda Duva; Sitorus, Parlindungan; Ndruru, Astri JUli Artaniman (Universitas Pendidikan Ganesha, 2023)
The learning process is still not optimal because the learning models and media used are still conventional. This study aims to determine the effect of the discovery learning model on student learning outcomes on pressure material with the help of Phet Interactive Simulation Media at SMP Negeri 13 Medan. The method and design used is pre-Experimental Design with One-Group Pretest-Posttest type. The population of this study is all students in class VIII with the research sample is class VIII-4 with the sample technique is purposive side. The results of hypothesis testing analysis obtained t count = 16.11 with a significant level of 5% and t table = 2.04, then Ha is accepted and Ho is rejected. The average obtained on the pretest was 28.5 on the posttest 70.17. Furthermore, to determine the effect of the discovery learning model on student learning outcomes, a regression test was conducted with the equation Y = 27.32 + 0.62X. It can be concluded that there is an influence and improvement in the learning outcomes of students in class VIII-4 SMP Negeri 13 Medan after using Phet Interactive Simulatin media in the discovery learning learning model.